Physical activity levels in normal weight and overweight portuguese children : an intervention study during an elementary school recess - Lopes, Luís Carlos Oliveira (2009)
This study aimed to analyze the effects of an intervention strategy during the school recess on physical activity (PA) levels, by gender, age and body mass index (BMI). The sample comprises 158 Portuguese children aged 6 to 12 years. Weight and height were objectively measured. PA was assessed by accelerometry during the recess in pre-intervention and post-intervention periods. Introduction of extra outdoor play equipment was used as an intervention strategy. Significant interaction effects were found for the following areas: percentage of time spent in PA (F(1,150)=70.157;p<0.001), intervention X age group (F(1,150)= 24.416;p<0.001) and gender X age group (F(1,150)=6.919;p=0.009); the time spent in Moderate PA for intervention X gender (F(1,150)=15.290;p<0.001) and BMI X gender (F(1,150)=6.411;p=0.012); the time spent in Vigorous and Very Vigorous PA (F(1,150)=54.790;p=0.001), intervention X age group (F(1,150)=9.490; p=0.002), intervention X gender (F(1,150)=14.161;p<0.001) and BMI X gender (F(1,150)=5.049;p=0.026). It appears that successful recess interventions to improve PA for children in elementary scholars are possible by providing relatively inexpensive play equipment.